MicroMagnify: A Multiplexed Expansion Microscopy Method for Pathogens and Infected Tissues - Zhangyu Cheng; Caroline Stefani; Thomas Skillman; Aleksandra Klimas; Aramchan Lee; Emma F. DiBernardo; Karina Mueller Brown; Tatyana Milman; Yuhong Wang; Brendan R. Gallagher; Katherine Lagree; Bhanu P. Jena; et al. (Advanced Science, 2023)
Abstract Super‐resolution optical imaging tools are crucial in microbiology to understand the complex structures and behavior of microorganisms such as bacteria, fungi, and viruses. However, the capabilities of these tools, particularly when it comes to imaging pathogens and infected tissues, remain limited. MicroMagnify (µMagnify) is developed, a nanoscale multiplexed imaging method for pathogens and infected tissues that are derived from an expansion microscopy technique with a universal biomolecular anchor. The combination of heat denaturation and enzyme cocktails essential is found for robust cell wall digestion and expansion of microbial cells and infected tissues without distortion. µMagnify efficiently retains biomolecules suitable for high‐plex fluorescence imaging with nanoscale precision. It demonstrates up to eightfold expansion with µMagnify on a broad range of pathogen‐containing specimens, including bacterial and fungal biofilms, infected culture cells, fungus‐infected mouse tone, and formalin‐fixed paraffin‐embedded human cornea infected by various pathogens. Additionally, an associated virtual reality tool is developed to facilitate the visualization and navigation of complex 3D images generated by this method in an immersive environment allowing collaborative exploration among researchers worldwide. µMagnify is a valuable imaging platform for studying how microbes interact with their host systems and enables the development of new diagnosis strategies against infectious diseases.